Business cycles, monetary transmission and shocks to financial stability: Empirical evidence from a new set of Danish quarterly national accounts 1948-2010 - Kim Abildgren (Danmarks Nationalbank, 2010)
In Denmark official quarterly national accounts are only available for the period since 1977. The paper constructs a set of summary non-seasonally adjusted quarterly national accounts for Denmark for 1948-2010 in current and constant prices as well as a set of other key quarterly macroeconomic indicators covering the Danish economy since 1948. As a first exploratory analysis of these two new data sets the paper reviews some of the stylised empirical evidence on the business cycle, the monetary transmission mechanism and shocks to financial stability that can be uncovered using filtering techniques and reduced-form vector autoregressive (VAR) models. The long-span data sets make it possible to estimate VAR models of a higher dimension than is usually found in the literature due to degrees-of-freedom problems. The results from the VAR analysis indicate a significant and long-lasting negative impact on real GDP following an exogenous shock to the banking sector's write-down ratio.
Keywords: C32; C82; E01; E32; E44; E52; N14; 330; Quarterly national accounts; Danish economic history; business cycles; monetary transmission; financial stability; band-pass filters; VAR analysis; Konjunktur; Finanzmarkt; Geldpolitische Transmission; Zahlungsbilanz; VAR-Modell; Dänemark